Development of Multiple Choice Learning Evaluation based on Automatic Assessment of Hydrosphere Material - Budi, Ridha Sulistyo; Aldina Eka, Andriani (Universitas Muhammadiyah Ponorogo, 2025)
The preparation of learning evaluations that refer to variations in the form of questions, variations in question stimuli, and variations in cognitive levels and utilize technology has not been optimally carried out by teachers. This study aims to describe the design, test the feasibility, and effectiveness of the development of multiple choice learning evaluation based on automatic assessment of hydrosphere material. The type of research is Research and Development (R&D) using the Borg and Gall model. The research subjects were 27 VA class students of Purwoyoso 04 State Elementary School. Data collection techniques used non-tests (observation, interviews, questionnaires, and documentation) and tests (pretest and post-test). Data analysis techniques used normality test, t test, and N-Gain test. The results of this study show: The development design of multiple choice learning evaluation based on automatic assessment with variations in the form of multiple choice questions (ordinary multiple choice and complex multiple choice), variations in question stimulus (text, image, video, audio and table), with MOTS cognitive level (for C3 cognitive level) and HOTS (for C4 and C5), and using quizizz application; The feasibility of developing multiple choice learning evaluations based on automatic assessment from material experts is 92.18% and media experts are 91.66% very feasible criteria supported by the results of a 100% teacher response questionnaire and 100% learner response with very feasible criteria; the effectiveness of multiple choice learning evaluations based on automatic assessment is shown from the increase in pre-test and post-test scores by 33.3, the t-test results show the significance value (2-tailed) is